Nikita Lary and Jay Leyda (eds.): The Alexander Medvedkin Reader - Schwarz, Alexander (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
Alexander Schwarz's review of Nikita Lary and Jay Leyda's edited book The Alexander Medvedkin Reader